Art of The First Cities: The Third Millennium B.C. from The Mediterranean to The Indus - Joan Aruz; Ronald Wallenfels (USA The Metropolitan Museum of Art, 2003)
Our civilization is rooted in the forms and innovations of societies that flourished more than six thousand years ago in distant lands of western Asia, extending from Egypt to India. The earliest of these societies was in the region known to the ancients as Mesopotamia, which occupies what is today Iraq, northeastern Syria, and southeastern Turkey. In Mesopotamia arose the first cities, and here urban institutions were invented and evolved. Writing was invented, monumental architecture in the form of temples and palaces were created, and the visual arts flowered in the service of religion and royalty. These extraordinary innovations profoundly affected surrounding areas in Anatolia, Syria-Levant, Iran, and the Gulf. Mesopotamia was influenced in turn by these outlying regions, for as networks of trade emerged they encouraged cultural exchange. This publication explores the artistic achievements of the era of the first cities in both the Mesopotamian heartland and across the expanse of western Asia. More than fifty experts in the field have contributed entries on individual works of art and essays covering a wide range of subjects. Among the objects presented are many that display the pure style of Mesopotamia, others from outlying regions that adapt from Mesopotamian models a corpus of forms and images, and still others that embody vital regional styles. Included are reliefs celebrating the accomplishments of kings and the pastimes of the elite; votive statues representing royal and other privileged persons; animal sculptures; and spectacular jewelry, musical instruments, and games found in tombs where kings, queens, and their servants were buried. -- Metropolitan Museum of Art website
Catalog of an exhibition held at the Metropolitan Museum of Art, New York, May 8-Aug. 17, 2003
Exhibition title: Art of the first cities : the third millennium B.C. from the Mediterranean to the Indus
Keywords: Art, Ancient -- Middle East -- Exhibitions; Civilization, Ancient -- Exhibitions; Cities and towns, Ancient -- Middle East; General